T-cell lymphoma with abundant CD20 expression showing a good response to rituximab with gemcitabine, oxiplatin, and L-asparaginase (R-pGEMOX): A case report. Issue 12 (March 2018) - Shao, Yajuan; Bai, Chunmei; Sun, Jian; Gao, Xin
Abstract: Rationale: T-cell lymphoma is a neoplasm that expresses markers of T-cell or natural killer cell (NK)-origin but not those of B-cell origin. Although B-cell lymphoma with abundant expression of T-cell markers exist, the opposite is very rare. Therefore, little is known about this subtype of lymphoma, including its treatment and prognosis. Case report: A 65-year-old man was diagnosed with T-cell lymphoma with abundant CD20 expression. He was refractory to cyclophosphamide + epirubicin + vincristine + prednisone + etoposide (CHOPE), ifosfamide + cisplatin + etoposide + dexamethasone (DICE), and hyper-cyclophosphamide + vincristine + epirubicin + dexamethasone (CVAD) chemotherapy. The patient was also treated with prednisone + thalidomide + chidamide, which was also not effective. Upon admission to our department, he was administered a rituximab + gemcitabine + oxiplatin + L-asparaginase (R-pGEMOX) regimen and achieved partial remission. Lessons: CD20-positive T-cell lymphoma is a very rare type of lymphoma that is refractory to CHOP-like regimens alone. Rituximab may be effective in patients showing abundant CD20 expression, and an R-pGEMOX regimen will likely be effective, even in refractory/recurrent patients.